A avaliação da aprendizagem escolar de estudantes com deficiência intelectual - Terra, Maria Lúcia [UNESP] (2014)
This Master‘s thesis is bounded to the research‘s line of Educational Practices and Teacher Education, of Post-Graduatied Program in Education, Faculty of Sciences and Technology, UNESP. It has as initial hipothesis the assumption of education systems in general, still have several doubts and insecurities related to the execution of evaluation processes that are able to promote high quality inclusive education for students with intellectual disabilities. The general objective is to analyze the process of learning assessment of students with intellectual disabilities, at regular class and at SRM of AEE, in four municipal schools of São Paulo/Brasil, seeking to identify the implications of this assessment for the development of these students. The theoretical framework consists of the conceptions of formative and mediator assessment, assumptions of culturalhistorical theory and the and principles of special education in the perspective of inclusive education...